2021
DOI: 10.1002/ps.6469
|View full text |Cite
|
Sign up to set email alerts
|

A novel encapsulation of Streptomyces fulvissimus Uts22 by spray drying and its biocontrol efficiency against Gaeumannomyces graminis, the causal agent of take‐all disease in wheat

Abstract: BACKGROUND Wheat is a valuable food source that is exposed to many diseases that reduce its quantity and quality. One of the most important diseases affecting wheat is take‐all, caused by Gaeumannomyces graminis var. tritici. The application of bacterial inoculants into the soil can increase plant nutrient absorption and enhance the efficiency of probiotic bacteria. For increased beneficial bacteria efficiency, the encapsulation technique has been used in agriculture. RESULTS The results of Fourier transform i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…Although ideal bacterial agents have been reported during laboratory screenings, their application in the field has not been very successful. One of the reasons for this lack of success can be considered the adverse effect of environmental factors (including salinity stress) on the bacteria used, which reduces their efficiency and may kill them [7,8]. To increase their viability and improve their performance, it is necessary to add a suitable formulation of these factors in the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Although ideal bacterial agents have been reported during laboratory screenings, their application in the field has not been very successful. One of the reasons for this lack of success can be considered the adverse effect of environmental factors (including salinity stress) on the bacteria used, which reduces their efficiency and may kill them [7,8]. To increase their viability and improve their performance, it is necessary to add a suitable formulation of these factors in the soil.…”
Section: Introductionmentioning
confidence: 99%
“…This method also produces a very fine powder, and it is unsuitable for heat-sensitive material. Saberi-Riseh and Moradi-Pour [95] reported that the number of Streptomyces fulvissimus Uts22 bacteria in chitosan-gellan gum microcapsules obtained by this method was approximately 10 8 CFU g −1 after storage for 2 months. method are the restriction in the selection of wall materials and the lack of microcapsule uniformity [95].…”
Section: Spray-drying Techniquementioning
confidence: 94%
“…Saberi-Riseh and Moradi-Pour [95] reported that the number of Streptomyces fulvissimus Uts22 bacteria in chitosan-gellan gum microcapsules obtained by this method was approximately 10 8 CFU g −1 after storage for 2 months. method are the restriction in the selection of wall materials and the lack of microcapsule uniformity [95]. This method also produces a very fine powder, and it is unsuitable for heat-sensitive material.…”
Section: Spray-drying Techniquementioning
confidence: 94%
See 1 more Smart Citation
“…A mixture of xanthan-gellan gum can be used to encapsulate PGPR [43,44,128], the granules produced from a mixture xanthan-gellan gum are resistant to acidic conditions, unlike the granules obtained from alginates [70]. Saberi-Riseh and Moradi-Pour [61] encapsulated Streptomyces fulvissimus Uts22 in chitosangellan gum beads.…”
Section: Xanthan and Gellan Gummentioning
confidence: 99%